Motivating students with projects encompassing the whole duration of their studies - Pánovics, János (Teaching Mathematics and Computer Science, 2013)
Based on my ten years of teaching experience at the University of Debrecen, I can say that students majoring Software Information Technology BSc have to face a number of difficulties during their studies. I think these difficulties root from two main problems: students are unmotivated and cannot sense the coherence between the knowledge acquired in the various courses. This paper tries to give some alleviation to both of these problems by the idea of introducing some long-term projects to students, which they can work on throughout their studies, dealing with a particular aspect of the projects in each course.